Odpowiedź :
1.
[tex](-2\frac{1}{2})^{2} =(-\frac{5}{2})^{2} = \frac{(-5)^{2}}{2^{2}} = \frac{25}{4} = 6\frac{1}{4}\\\\Odp. \ C.[/tex]
2.
[tex]a = (\frac{5}{2})^{18} = 2,5^{18} \ \ IV\\\\o = (\frac{2}{5})^{18} = 0,4^{18} \ \ I\\\\p = (\frac{2}{5})^{16} = 0,4^{16} \ \ II\\\\r = (\frac{5}{2})^{16} = 2,5^{16} \ \ III\\\\(\frac{2}{5})^{18} < (\frac{2}{5})^{16} < (\frac{5}{2})^{16} < (\frac{5}{2})^{18}\\\\Odp. \ D. \ o, p, r, a.[/tex]
3.
[tex]-2^{4}-(-3^{2}\cdot2 = -16-9\cdot2 = -16-18 = -34\\\\Odp. \ B.[/tex]
4.
A.
[tex](-5)\cdot(-5) \ ? \ 5^{2}\\\\(-5)\cdot(-5) = 5^{2}[/tex]
B.
[tex]2^{6}+2^{6} \ ? \ 2^{7}\\\\2\cdot2^{6} = 2^{7}[/tex]
C.
[tex]7^{8}-(-1)^{5} \ ? \ 7^{8} - 1\\\\7^{8}+1 \neq 7^{8}-1[/tex]
D.
[tex]1^{5}+0^{5}-5^{0} \ ? \ 0\\\\1+0-1 = 0\\\\Odp. \ C.[/tex]